Módulos Cohen-Macaulay maximais sobre anéis de Gorenstein e sequências de Bourbaki - Azerêdo, Aiury Silva (2021)
The purpose of this work is to investigate some results due to J urgen Herzog and Michael K uhl, published in 1987 in their classic paper Maximal Cohen-Macaulay Modules over Gorenstein Rings and Bourbaki-Sequences. We concentrate our attention on maximal Cohen-Macaulay modules over a local Gorenstein domain, prove general facts about it and we also explore the case when the base ring is a hypersurface. Finally, we present the main result, which connects the notion of Bourbaki-Sequences to the algebraic linkage concept.